Formulation and Evaluation of Ezetimibe Nanoparticles - Yasser A.Ali; Shaimaa N. Abd-Alhammid (College of Pharmacy University of Baghdad, 2017)
The aim of this study is to formulate and evaluate ezetimibe nanoparticles using solvent antisolvent technology. Ezetimibe is a practically water-insoluble drug which acts as a lipid lowering drug that selectively inhibits the intestinal absorption of cholesterol and related phytosterols. Ezetimibe prepared as nano particles in order to improve its solubility and dissolution rate. Thirty formulas were prepared and different stabilizing agents were used with different concentrations such as poly vinyl pyrrolidone (PVPK-30), poly vinyl alcohol (PVA), hydroxy propyl methyl cellulose E5 (HPMC), and poloxamer. The ratios of drug to stabilizers used to prepare the nanoparticles were 1: 2, 1:3 and 1:4. The prepared nanoparticles were evaluated for particle size, entrapment efficiency, dissolution study, Fourier transform infrared spectroscopy, differential scanning calorimetry, and atomic force microscopy. The percentage of drug entrapment efficiency of F1-F30 was ranged from 85% Â± 1 to 98 % Â± 1. On the other hand dissolution rate increasing as the particle surface area is increase due to reduction of particle size to the nano range. The results showed that poly vinyl pyrrolidone (PVPK-30) was found to be the best stabilizer.  Keywords: Ezetimibe, Nanoparticles, Particle Size, poly vinyl alcohol.